2018
DOI: 10.1002/cbdv.201700567
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenes and Meroterpenes with Neuroprotective Effects from Ganoderma leucocontextum

Abstract: Ganoderma leucocontextum is a well-known medicinal mushroom cultivated in the Tibet Plateau of China. Chemistry investigation on the fruiting bodies of this mushroom resulted in the isolation of sixteen secondary metabolites including three new lanostane triterpenes, ganoleucoins Q - S (1 - 3), as well as thirteen known compounds (4 - 16). The structures of compounds 1 - 3 were determined by NMR, MS, CD spectral analysis, and chemical derivation method. The neuroprotective effects of compounds 1 - 16 were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…The steady-state activation curve of I h in the presence of GTs was shifted along voltage axis toward the less depolarized potential. The IC 50 value (i.e., 11.7 µg/mL) required for GTs-mediated inhibition of I h observed in GH 3 cells is similar to that used for anti-oxidative or neuroprotective properties [2,3,4,15,16,17,46,47]. Such intriguing actions could be of pharmacological relevance and appear to be upstream of its effects on oxidative stress occurring inside the cell.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The steady-state activation curve of I h in the presence of GTs was shifted along voltage axis toward the less depolarized potential. The IC 50 value (i.e., 11.7 µg/mL) required for GTs-mediated inhibition of I h observed in GH 3 cells is similar to that used for anti-oxidative or neuroprotective properties [2,3,4,15,16,17,46,47]. Such intriguing actions could be of pharmacological relevance and appear to be upstream of its effects on oxidative stress occurring inside the cell.…”
Section: Resultsmentioning
confidence: 67%
“…Triterpenoids have molecular weights ranging from 400 to 600 kDa, and their chemical structure is complex and noted to be highly oxidized [9]. The triterpenoid fraction of Ganoderma , consisting of more than 300 lanostane-tetracyclic compounds, has been growingly demonstrated to be effective at exerting an array of biological actions such as that known either to provide effective antioxidant activities for prevention of myocardial injury, or to produce neuroprotective actions [2,3,4,5,6,10,11,12,13,14,15,16,17,18,19,20,21]. Ganoderma triterpenoids (GTs) could also suppress inflammatory response by directly scavenging the free radicals or systemically enhancing the antioxidant enzymes, thereby lowering lipid peroxidase in chicken livers or mice [2,3,8,17,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The aromatic meroterpenoids have attracted the attention of many phytochemists, chemists, and pharmocologists, due to their diverse structures and significant bioactivities (antioxidant, anti-HIV protease, and antifibrotic activities) [13,14,15,16]. Meanwhile, some oxygenated lanostane triterpenoids also showed potent free radical scavenging activities and neuroprotective activity [17,18]. These previous studies suggested Ganoderm mushrooms might be a novel resource for natural antioxidant exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Ganoderma leucocontextum, called "Bai-Rou-Ling-Zhi (白肉灵芝)" with white context, has been regarded as folk medicine in the Southwestern China for the prevention and treatment of various diseases. In the last five years, it has been reported that its bioactive compounds have various effects, including anti-diabetic, antitumor, neuroprotective, pancreatic lipase inhibition [31][32][33]. In this study, we found that ethanol extract and active fraction (GLEA) inhibited cancer growth in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 70%
“…The fruit bodies of Ganoderma leucocontextum have been used in folk medicine in the prevention and treatment of diseases. Bioactive compounds isolated from Ganoderma leucocontextum were mainly lanostane triterpenes, which have several biological activities, including anti-tumor growth, inhibition of HMG-CoA, inhibition of pancreatic lipase, and neuroprotective activities [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%